Assessing dynamic coastal vulnerability to climate hazards: A geospatial approach in Kakinada District, Andhra Pradesh, India - Ganni Satya Venkata Sai Aditya Bharadwaz; Indrajit Pal; Chitrini Mozumder; Mokbul Morshed Ahmad (Environmental and Sustainability Indicators)
This study assesses the dynamic coastal vulnerability of Kakinada district in India by integrating various geophysical and socioeconomic factors within a geospatial framework. The analysis examines data from 2001, 2011, and 2021, evaluating dynamic components like cyclone track density, tsunami surge, coastal erosion, temperature rainfall, population, land use/land cover, elevation, slope and drainage density, and transport network. The findings indicate that coastal residents are at high risk due to climate change and coastal hazards. The composite assessment of dynamic coastal vulnerability was estimated and mapped annually, revealing significant impacts across the district. In 2021, 91.17 km2 of coastal tracts in Thallarevu, Kakinada Urban, Kakinada Rural, Kothapallei, and Thondangi were classified as very high vulnerability zones. An additional 239.98 km2 was categorized as high vulnerability and 267.17 km2 as moderate vulnerability. Overall, 598.32 km2 out of 1647.68 km2 exhibited moderate to very high vulnerability, highlighting the threats from coastal erosion and human encroachment. Significant coastal erosion was identified, with shoreline changes ranging from 604.35 to 1016.25 m over the past two decades, particularly in the southern district. Sea level rise was a critical factor, especially in Kajuluru and Thallarevu, and rapid population growth and urban development exacerbated vulnerability by reducing vegetation cover and increasing built-up areas. Thondangi and Kakinada urban were identified as the most vulnerable blocks, requiring urgent adaptation and mitigation strategies. The study recommends enhancing local services such as clean water, sanitation, primary healthcare, skill development, and flood shelters linked by efficient transportation networks could improve living standards and reduce vulnerability.